2011
DOI: 10.1037/a0024341
|View full text |Cite
|
Sign up to set email alerts
|

Music-induced context preference following cocaine conditioning in rats.

Abstract: Traditional models of drug-seeking behavior have shown that exposure to associated environmental cues can trigger relapse. These learned associations take place during repeated drug administration, resulting in conditioned reinforcement. Although considerable investigation has occurred regarding simple conditioned stimuli, less is known about complex environmental cues, particularly those that may be salient in human addiction. Recent studies indicate that music can serve as a contextual conditioned stimulus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…To mimic the intricate psychological processes that occur during human drug experiences, we utilized a complex contextual cue to assess associative learning processes that occur during craving. Complementing previous work (Polston and Glick, 2011; Polston et al, 2011), the present findings further support the notion that rats have the capacity to distinguish complex musical passages, and suggest that rats could be used in other preclinical models involving musical interventions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To mimic the intricate psychological processes that occur during human drug experiences, we utilized a complex contextual cue to assess associative learning processes that occur during craving. Complementing previous work (Polston and Glick, 2011; Polston et al, 2011), the present findings further support the notion that rats have the capacity to distinguish complex musical passages, and suggest that rats could be used in other preclinical models involving musical interventions.…”
Section: Discussionsupporting
confidence: 88%
“…It could be argued that we should have employed a CS- paired with a different musical selection in order to test the specificity of our music-induced reinstatement. However, in previous investigations we have paired both the Miles Davis song used here, and Beethoven’s “Fur Elise” with saline, and have never seen a behavioral or neurochemical effect (Polston and Glick, 2011; Polston et al, 2011). It is also possible that our results could have been influenced by the fact that we used female rats for this investigation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is the first demonstration of CPP in humans that measured actual time spent in either context in a free choice procedure. In rats, while music can be used as a conditioned stimulus to establish cocaine-induced CPP, music alone does not appear to induce CPP (Polston & Glick, 2011). Thus, humans may be unique it their propensity to find music to be rewarding.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the stimuli used to establish CPP or CPA, laboratory animal research has shown that sound and music can be used to enhance the rewarding effect of 3,4-methylenedioxymethamphetamine (MDMA; Feduccia & Duvauchelle, 2008), as well as serving as conditioned stimuli to induce cocaine-induced CPP (Polston & Glick, 2011). Therefore, we decided to use music for the sake of simplicity and for practical reasons.…”
mentioning
confidence: 99%